Determinan Stigma Siswa/I Terhadap Orang Dengan HIV/AIDS (ODHA) Berdasarkan Theory Of Planned Behavioral Di SMAN 10 Kabupaten Gowa - Fatiah Nabila Syaidina; Andi Asrina; Fatmah Afrianty Gobel (Window of Public Health Journal, 2026)
HIV is a virus that attacks the human immune system, especially Cluster of Differentiation 4 (CD4) cells. If not treated properly, it will cause AIDS, a syndrome that appears due to HIV infection. Based on data from the Gowa Health Office, it was recorded that until October 2024, there were 137 positive cases of HIV in Gowa Regency. The discovery of cases in Indonesia, which is increasing every year, is concerning and needs to be closely monitored to understand why it is happening. One of these is because of stigma and discrimination. In this context, high school students are an important group to consider because they are in a crucial phase of psychosocial development. Adolescence is a transitional period in which they generally seek identity by trying new things out of curiosity. This study is quantitative and cross-sectional. This study involved students at SMA Negeri 10 Gowa with a sample of 147 respondents. The data analysis method used was bivariate analysis with a chi-square correlation test using SPSS. The results of the study showed that there was an influence between attitudes and subjective norms on student stigma towards people with HIV/AIDS (ODHA). Moreover, there is no influence between perceived behavioral control and students' stigma towards people with HIV/AIDS (ODHA).